Influence of molar incisor hypomineralisation severity on dental hypersensitivity, anxiety/fear, and aesthetic self-perception: a cross-sectional study - Bianca Caroline GOMES; Lana CARDOSO-SILVA; Beatriz Kelly Barros LOPES; Roberta Paula de Faria MELO; Isabella Silva CATANANTI; Alexandra Mussolino de QUEIROZ; Francisco Wanderley Garcia PAULA-SILVA; David John MANTON; Fabrício Kitazono de CARVALHO (Journal of Applied Oral Science, 2025)
Abstract Molar-incisor hypomineralisation (MIH) significantly impacts children's quality of life due to dental hypersensitivity, anxiety, and aesthetic concerns. Few studies have investigated these factors within the same sample, comparing varying levels of MIH severity to MIH-free controls. Objectives: This study evaluated dental hypersensitivity, anxiety, and aesthetic self-perception in children with mild MIH, severe MIH, and controls, and explored correlations between the studied variables. Methodology: A total of 605 students from a single school were evaluated: 110 children with MIH and 214 controls matched by age and sex. MIH severity was clinically assessed using the Ghanim criteria. Hypersensitivity was measured with the visual analogue scale (VAS) and the Schiff Cold Air Sensitivity Scale (SCASS). Anxiety and aesthetic concerns were assessed using the CFSS-DS and CQATA questionnaires, respectively. Results: Overall, 78 children had mild MIH and 32 had severe MIH. Median for dental hypersensitivity (p<0.001) and aesthetic self-perception (p=0.002) were significantly higher in the severe MIH group compared to both the control and mild MIH groups. No differences were found for anxiety. Elevated VAS-measured dental hypersensitivity levels and impaired self-perceived aesthetics were significantly correlated with greater MIH severity (p<0.05). Spearman's correlation analysis further revealed significant positive correlations between anxiety/fear and VAS scores (p=0.023, r=0.239), between anxiety/fear and aesthetic self-perception scores (p=0.007, r=0.282), and between dental appearance classification and VAS hypersensitivity scores (p=0.035, r=0.222). In contrast, SCASS hypersensitivity scores did not significantly correlate with either anxiety/fear or dental appearance classification (p>0.05). Conclusions: Children with severe MIH showed higher dental hypersensitivity and greater perceived aesthetic impairment than children with mild MIH or without MIH.